Application of Health Communication for the Prevention of Leptospirosis in the Community - Marisca Jenice Sanaky (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Health communication is a systematic effort to positively influence the health behavior of individuals and health communities. Health communication applied as prevention of leptospirosis disease transmission in the Ma’rang subistrict, Pangkep regency. Leptospirosis is a disease caused by rats urine contaminated by leptospira bacteria, the disease is contagious and deadly. The problem is that until now the District community does not know how to prevent the spread of leptospirosis transmission. Researchers chose the practice of health communication application which was held in the Pitue village, Ma’rang subdistrict, Pangkep regency for the prevention of leptospirosis. By taking this case, the application of health communication can be analyzed. Patterns and strategies that can be applied to a reference to see the implementation of health communication.This research is coundueted descriptive case study method. Object of research is the application of health communication practices for the prevention of leptospirosis that were performed in Pitue village, Ma’rang subdistrict, Pangkep Regency. The results showed that the application of health communication was influenced by three aspects, namely input, process and output. Health communication proved to bring about change in knowledge, attitudes and behavior in response to leptospirosis